Thermal treatment of municipal solid waste (MSW) - Paunovic, Perica; Hadzi-Jordanov, Svetomir (Macedonian Journal of Ecology and Environment, 2001)
Thermal treatment, especially high-temperature incineration, is the most frequently used alternative process for Municipal Solid Waste (MSW) treatment. The goals of this process are reduction of MSW volume (about 90%) and waste-to-energy conversion and utilization. In this paper, the following aspects of thermal treatment are given: thermal characteristics of MSW, incineration parameters, thermal treatment facilities and further treatment of solid residues and emitted gases. Also, the basic characteristics of pyrolitic and combinied processes are described.